TUJUAN PENDIDIKAN ISLᾹM MENURUT OMAR MOḤAMMAD AL-TOUMY AL-SYAIBANY DAN IMPLIKASINYA TERHADAP PEMBELAJARAN PAI DI SEKOLAH - Hanifah Adesty, - (2019)
Penelitian ini dilatarbelakangi oleh pentingnya tujuan pendidikan Islām dirumuskan berdasarkan falsafah pendidikan Islām yang kuat. Berdasarkan temuan di lapangan, tujuan pendidikan Islām belum banyak yang dilandasi dengan falsafah pendidikan Islām. Hal tersebut disebabkan karena masih kurangnya teori yang ada dalam bidang falsafah pendidikan Islām. Tujuan penelitian ini untuk mendeskripsikan tujuan pendidikan Islām menurut Omar Moḥammad al-Toumy al-Syaibany dan Implikasinya terhadap Pembelajaran PAI di Sekolah. Penelitian ini menggunakan pendekatan kualitatif dan metode studi literatur. Peneliti mengumpulkan data dari berbagai sumber, baik sumber primer maupun sumber sekunder. Setelah data terkumpul, kemudian peneliti melakukan analisis data dengan melakukan analisis isi, dan interpretasi data. Tahapannya, peneliti melakukan analisis metode deskriptif historis dalam rangka mendeskripsikan pandangan Al-Syaibany berkaitan dengan tujuan pendidikan Islām. Setelah itu, peneliti melakukan penyimpulan terhadap data yang telah dianalisis dengan metode pengambilan kesimpulan induktif. Berdasarkan hasil penelitian, tujuan pendidikan Islām menurut al-Syaibany terdiri dari konsep tujuan pendidikan Islām, tahap-tahap tujuan pendidikan Islām, ciri-ciri dan prinsip-prinsip tujuan pendidikan Islām, sumber yang menjadi dasar tujuan pendidikan Islām, tujuan umum individu dan tujuan umum sosial, dan implikasinya terhadap pembelajaran PAI di Sekolah. Konsep tujuan pendidikan Islām menurut al-Syaibany memiliki konsep yang jelas dan komprehensif, gagasan tersebut sangat baik jika diterapkan dalam pembelajaran PAI. Tujuan PAI juga selaras dengan tujuan pendidikan Islām menurut al-Syaibany yakni mencakup ranah individu, sosial dan profesional. Implikasi keduanya terletak pada tujuan hidup manusia, dimana PAI bertujuan untuk mengarahkan manusia dalam pencapaian tujuan hidup yang sebenarnya yaitu mencapai kebahagiaan dunia dan akhirat. Sumber pendidikan keduanya sama yaitu Alqur'ān dan Sunnah menjadi rujukan utama dalam perumusan tujuan pendidikan Islām.; This research is motivated by the importance of the purpose of Islāmic education that is formulated based on the strong philosophy of Islāmic education. Based on the findings, many Islāmic education objectives are still not based on the Islāmic education philosophy. This is due to lack of theory in the field of Islāmic education philosophy. The purpose of this study is to describe the purpose of Islāmic education according to Omar Moḥammad Al-Toumy Al-Syaibany and their implications on the learning of Islāmic Education in Schools. This study employed a qualitative approach and literature study method. The researcher collected data from various sources both primary and secondary sources. After the data was collected, the researcher analyzed the data by studying the contents and interpreting the data. The stages include conducting an analysis on the historical descriptive method in order to describe Al-Syaibany's view related to the purpose of Islāmic education. Afterwards, the researchers drew a conclusion of the data that has been analyzed by inductive-concluding method. Based on the results of the study, the aim of Islāmic educationaccording to al-Syaibany consisted of the concept of the purpose of Islāmic education, stages of Islāmic education goals, characteristics and principles of Islāmic education goals, sources that form the foundation of Islāmic education goals, individual and social general objectives, and their implications towards the learning Islāmic of Education in schools. The objectives of Islāmic education concept according to al-Syaibany are clear and comprehensive. The idea is very proper if applied in the learning of Islāmic Education. The aim of Islāmic Education is also in harmony with the educational objectives in the perspective of al-Syaibany which include individual, social, and professional domains. The implication of both lies in the purpose of human life, in which Islāmic Education aims to guide humans in achieving the real life goals namely attaining happiness in the world and the hereafter. The educational sources of both are the same namely Alqur'an and Sunnah as the main references in the formulation of educational objectives. The purpose of Islāmic education according to al-Syaibany also have implications on the planning, implementation, and evaluation of the learning of Islāmic Education in schools. This is in line with the principles of Islāmic education hich was initiated by al-Syaibany, which must be applied to the process of planning, implementing and learning evaluation.